Pengaruh Pemberian Aromaterapi Peppermint Dan Terapi Akupresur Titk L14 (Hegu) Terhadap Tingkat Nyeri Ibu Bersalin Kala 1 Fase Aktif Di SMC RS Telogorejo - Faulida Wahyuningrum; Ns. Anis Ardiyanti; Diffa Risqa Arisdiani (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Labor pain refers to sensory and emotional experiences since the early phase of laboring. One of the indications is continuous and progressive contraction. This matter causes enormous pain in the first active phase. Pain without management may influence the delivery process. Thus, pain management is important to relieve the pain. The administration of peppermint aromatherapy and acupressure therapy on the L14 point, the hegu point, could relieve the labor pain. This research determined the influence of peppermint aromatherapy and the L14 acupressure point, the high point, toward the labor pain of mothers with the first active phase at SMC Telogorejo. This quasi-experimental research applied a pretest-posttest deign without a control group. The applied sampling technique was consecutive. The obtained samples were 31 respondents. 28 respondents were aged between 20 and 35 years old, 90.3%. Respondents with multipara status were 20 respondents, 64.5%. Most respondents graduated from high educational levels, with 26 respondents (83.9%). the respondents also mostly worked, 17 respondents (54.8%). The Wilcoxon test obtained a p-value of 0.000 ≤ 0.05. The results showed peppermint aromatherapy and L14 acupressure, the hegu, could relieve the pain level of mothers with the first active phase. The researcher expects future researchers to calculate the duration of the managed pain after the intervention.